Sorrow and the pity [videorecording (DVD)] : chronicle of a French city under the Occupation - Ophüls, Marcel; Harris, André, 1933- (Milestone cinematheque., 2011)
Through interviews with participants and newsreel footage, examines the occupation of France by the Germans during World War II as it occurred in the French city of Clermont-Ferrand. Concentrates on the themes of collaboration and resistance.